Impacts of Covid-19 on Migrants and Refugees - Baitha, Subhash Kumar; Tyagi, Rinkal; Chatterjee, Souvik (Jurusan Ilmu Politik Universitas Bangka Belitung, 2022)
Since the 1970s, in the aftermath of new social movements, the concept of refugees and migration in international politics has dominated both the academic discipline and public debates. According to the United Nations High Commissioner for Refugees, more than 82.4 million people worldwide were forcibly displaced from their homes by the end of 2020, either as internally displaced persons (IDPs) or as refugees, as a result of violent conflict, persecution, famine, or natural disasters. Even in normal times, the lives of refugees and migrants are fraught with difficulties, but in the midst of an pandemic like Covid-19, this problem has taken on new dimensions. The only way to avoid the pandemic is to take precautions and maintain a safe distance from one another. These precautions are extremely difficult for refugees and migrants to take amidst a global pandemic. Keeping in mind the international efforts and the problems faced by refugees and migrants, this paper is an attempt to comprehend the challenges faced by refugees and migrants during Covid-19 and what global efforts have been made to mitigate the pandemic's impact on refugee and migrant life.